2020
DOI: 10.1021/acs.jpcc.0c00525
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Understanding of NO2 Dissociation on a Rutile TiO2 (110) Surface: An Electronic Structure Study

Abstract: Understanding the mechanism of NO 2 interaction on semiconductor surfaces such as TiO 2 is a key step in designing the catalytic processes for conversion of NO 2 to useful products. In the present work, through density functional theory calculations and NEB simulations, we have performed a comprehensive electronic structure study and established the reaction steps for efficient conversion of NO 2 to HONO on TiO 2 surface in the presence of water vapor. We predict the dimerization of NO 2 to form a metastable N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…Both of their surfaces yield significantly more exothermic binding energies than our 3–4–2B structure with the binding of an O vacancy site in the defect-rich model resulting in binding energies substantially more exothermic than the binding of Ti without O vacancies. All other reports of this structure , are generally consistent with our 3–4–2B value. Rodriguez et al predicted a structure with two sites bridged by an N and O of NO 2 , with a much higher binding energy than our rotated HONO-like 3–4–1Tc .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Both of their surfaces yield significantly more exothermic binding energies than our 3–4–2B structure with the binding of an O vacancy site in the defect-rich model resulting in binding energies substantially more exothermic than the binding of Ti without O vacancies. All other reports of this structure , are generally consistent with our 3–4–2B value. Rodriguez et al predicted a structure with two sites bridged by an N and O of NO 2 , with a much higher binding energy than our rotated HONO-like 3–4–1Tc .…”
Section: Resultssupporting
confidence: 93%
“…We now compare previously calculated binding energies in the literature for TiO 2 bulk solid with our cluster calculations (Table ). Calculated LBEs from our CCSD­(T)/aD//B3LYP/aD (TiO 2 ) 3 cluster calculations are generally consistent with LBEs calculated using embedded cluster models, small cluster models, and plane-wave models , of rutile and anatase TiO 2 . Our physisorption LBEs for TiO 2 clusters are more exothermic than those reported in the literature for bulk solids.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…They concluded that NO 2 adsorption is in physisorptive without water. Another key finding is that the antibonding orbital population between Ti and On atoms has been found insignificant from the COHP figures [33] …”
Section: Introductionmentioning
confidence: 99%